Ensino de biologia na perspectiva da astrobiologia: origem e evolução da vida no planeta terra - Brito, Gleide Miriam Falcão (2021)
This work discusses aspects of an interdisciplinary educational process in primary Education, in the implementation of subjects and concepts related to the Base Nacional Comum Curricular(BNCC). In view of the dissemination of Astrobiology in Basic Education, from topics such as Origin and Evolution of life, the general objective of the research is to build a didactic manual that enables an educational practice of an interdisciplinary nature in the teaching of Biology, with contribution to astronomy concepts. To achieve the general objective, four specific objectives were outlined. The research methodology has a qualitative approach, applied nature, exploratory character and it is based on action research. The activities were applied to students of the first gradeof Educação Profissional Integrada ao Ensino Médio (EPI) from Centro Estadual de Educação Profissional em Saúde do Centro Baiano located at city of Feira de Santana (Bahia). The educational product applied is the didactic kit, AstroBioBox: a Kit of activities on Astrobiology, built with indication of materials to be used in an interdisciplinary way and was applied. It was proposed with the aim of providing the student with greater knowledge of different objects and themes of everyday life, encouraging young people to dedicate themselves more to this field of knowledge. In addition, the didactical kit contains activities related to the favourable characteristics for a given planet containing life, the early and current Earth’s atmospheric composition, the Evolution of oxygen at terrestrial surface and astronomical phenomena that cause a mass extinction over the Earth’s history. It was initially designed to be applied in person, but due to the pandemic, the material was adapted to be used remotely. The structure presented in the Dissertation is for the presential context, but the adaptations for the remote/virtual form are also presented. Classified as an instructional manual, it is expected that the didactic kit will significantly contribute to the teaching of Biology and the dissemination of Astronomy in Basic Education.